2019
DOI: 10.1021/acssuschemeng.9b04833
|View full text |Cite
|
Sign up to set email alerts
|

Pine Extractives Strongly Affect Lignin Thermochemical Pathways

Abstract: Interactions between Pinus virginiana wood and the corresponding extractives played a large role in lignin thermochemistry and selectivity of lignin acidolysis pathways, as determined by thioacidolysis and biogenic formaldehyde analysis. Heating wood (dry wood, 200 °C, 10 min) generates formaldehyde, principally via lignin acidolysis; this was studied as a function of extractives removal. Formaldehyde generation in P. virginiana and P. radiata woods was substantially reduced by extractives removal, but extract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 30 publications
1
13
0
Order By: Relevance
“…We confirmed this in whole tissue, but the pathway selectivity is much lower, probably, because in situ lignin substructures exhibit a broader range of bond-rotational conformations than do dimeric models . The C2/C3 pathway selectivity is also strongly affected by wood extractives, for instance much more so in Pinus virginiana than in Liriodendron tulipifera . Since the formation of lignin-borne formaldehyde is facile and subject to catalytic manipulation, it is feasible that formaldehyde generation might always be associated with biomass processing that induces lignin acidolysis.…”
Section: Introductionsupporting
confidence: 56%
See 2 more Smart Citations
“…We confirmed this in whole tissue, but the pathway selectivity is much lower, probably, because in situ lignin substructures exhibit a broader range of bond-rotational conformations than do dimeric models . The C2/C3 pathway selectivity is also strongly affected by wood extractives, for instance much more so in Pinus virginiana than in Liriodendron tulipifera . Since the formation of lignin-borne formaldehyde is facile and subject to catalytic manipulation, it is feasible that formaldehyde generation might always be associated with biomass processing that induces lignin acidolysis.…”
Section: Introductionsupporting
confidence: 56%
“…Our prior work involved quantitation of lignin-borne formaldehyde generated during thermal processing of wood. , We found that lignin-borne formaldehyde accounts for a small percentage of lignin acidolysis, where two major and competing pathways occur. Considering β-O-4 linkages (β-aryl ethers), lignin acidolysis begins with benzyl cation formation; thereafter, either C2 or C3 cleavage (as in C6C2 vs C6C3 products) can occur .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Extractives are nonstructural phytochemicals and affect many wood properties and their variety and quantities can differ among softwoods and hardwoods (Jankowska et al, 2017;Quinteiro et al, 2019;Wan & Frazier, 2019). The content and composition of wood extractives is a relevant factor for in energy production since it influences volatile materials and compounds emitted to atmosphere during burning (Moulin et al, 2017;Wan & Frazier, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…The raw pine resin has high viscosity, low melting point, and selfsolidifies at about 160− 180 • C, which can be catalysed using an alcohol, although its polymerization has not yet been fully understood (Huang et al, 2018;Okon et al, 2017). Recent research on pine resin focuses on resin derivatives obtained by thermochemical processes (Aldas et al, 2020;Wan and Frazier, 2019) or in improving the tapping process (de Oliveira Junkes et al, 2019;Zas et al, 2020). In this work, the raw pine resin was used to impregnate two different fast-growing solid woods (Eucalyptus grandis Hill Maiden and Pinus elliottii Engelm) and in situ polymerized to improve their hygroscopic, chemical, morphological, mechanical, and thermogravimetric properties.…”
Section: Introductionmentioning
confidence: 99%